KOMPETENSI LITERASI DIGITAL PENDIDIK DI ERA SOCIETY 5.0 - Fadhila Humaira; Wedra Aprison (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
At this time, education began to experience major shifts and changes due to developing administrative and technical systems. Due to the disruption of society 5.0, the role of educators is starting to change and educators are no longer an important part of the educational dimension, educational activities are no longer related to the flow of technological and information advances. The world of education is developing very quickly, which requires teachers to carry out updates in terms of mental, interpersonal and abilities. The role of this research is teacher competency, with a focus on teacher competency in the Society 5.0 era. One important thing in creating high-quality, high-quality education and ready to compete in several aspects in welcoming the Era of Society 5.0, one of which is understanding the extent of the role of teachers' abilities in the global era. This research is included in the descriptive study research category, which is also known as library research. The first foundation and reference for this research is based on various data sources or text references from expert opinions. It is shown that in the midst of the era as part of the 5.0 societal revolution, a teacher must have strong skills and be actively involved in overcoming the challenges of the times very quickly, able to carry out his duties as a teacher who not only teaches, but is also able to transform his students into useful people, ideal, intelligent, active, innovative and creative in accordance with the industrial revolution Society 5.0.